Implementation of the Informative Educative Function of Christian Religious Instructors in North Sulawesi Province - Luma, Subaedah; Binilang, Benny; Ruindungan, Max (International Journal of Education, Information Technology, and Others, 2024)
The study descriptively analyzed the implementation of the functions of Christian Chaplain for the development of Christian Education in North Sulawesi. Qualitative research method was applied and software NVivo 14 was used for analyzing data. This study was aimed to investigate the application of the four functions of Christian chaplain, namely, informative-educative, consultative, advocative, and administrative, as stated in the Technical Guide of Christian chaplain Number 137 Year 2017. The result showed that Christian chaplains, generally, had not yet understood those functions, characterized by the conventional practice of chaplaincy, which is by conducting worship. Primarily, uncomprehending and lacking of managerial competency became the main reasons of the traditional practice. To be professional, in applying the informative, Christian chaplain had to include identification and evaluation stages as part of managerial competency. For consultative function, Christian chaplain need to apply consultation steps by Killman and Miltroff and applying 7 advocation step of the Open Society Foundations for advocacy, and Fayol stage of administration for administrative function. This study was expected to open the opportunity of policy redesigning concerning of recruitment, education and competencies